1998
DOI: 10.1002/(sici)1097-0207(19980930)43:2<365::aid-nme436>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static analysis of cracks using the hypersingular formulation of the Boundary Element Method

Abstract: A new methodology for computing dynamic stress intensity factors in the frequency domain based on the mixed boundary element method, a combination of the equations corresponding to the integral representations of displacements and tractions, is proposed and analysed. The expressions of hypersingular fundamental solution are presented and their singular parts extracted. Also, a discontinuous Singular-Quarter-Point element is constructed. Finally, various parametric computations and applications are described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…When x i ∈ Γ, both the SBIE and the HBIE contain singular integrals, being at most weakly singular those associated with U * , at most strongly singular (Cauchy Principal Value integrals) those associated with T * and D * , and at most hypersingular (Hadamard Finite Part integrals) those associated with S * . The treatment of those integrals for this problem is analogous to that of acoustics [11] and elastodynamics [33,15] problems. The treatment of the HBIE is based on a regularization process that requires the integrands (excluding the term r −2 ) belong to the Hölder function space C 1,α [30].…”
Section: Conventional and Dual Boundary Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When x i ∈ Γ, both the SBIE and the HBIE contain singular integrals, being at most weakly singular those associated with U * , at most strongly singular (Cauchy Principal Value integrals) those associated with T * and D * , and at most hypersingular (Hadamard Finite Part integrals) those associated with S * . The treatment of those integrals for this problem is analogous to that of acoustics [11] and elastodynamics [33,15] problems. The treatment of the HBIE is based on a regularization process that requires the integrands (excluding the term r −2 ) belong to the Hölder function space C 1,α [30].…”
Section: Conventional and Dual Boundary Element Methodsmentioning
confidence: 99%
“…After some algebraic manipulations using the relationships between wavenumbers given by Eqs. (12), (15), (19) and (22) …”
Section: Rayleigh Waves On a Permeable Free-surfacementioning
confidence: 99%
“…1 redefined as x 2 = x 1 , x 3 = x 2 , and x 1 = x 3 . Following [19] the displacements and the tractions are written as u 3…”
Section: The Non-hypersingular Traction Biementioning
confidence: 99%
“…We cite e.g. the works of Chirino and Abascal [3] (dual BEM), Fidelinski et al [11] (mixed BIEM) and non-hypersingular traction BIE derivations by Zhang and Gross [27], Zhang and Achenbach [25]. An interesting study on the accuracy and stability of hyper-singular traction BIEs can be found in Rangelov et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…For the numerical solution, each shear band has been subdivided into a number Q of elements. In order to describe the square-root singularity 25 , two different kinds of shape function have been adopted: quadratic function for the elements interior to the shear band and square-root function (the so called ‘quarter-point element’s’ 26 , 27 ) at the shear band tips.…”
Section: Boundary Integral Equation and Numerical Solutionmentioning
confidence: 99%